Reproduction of Celebes rainbowfish, Marosatherina ladigesi Ahl, 1936 in Pattunuang and Batu Puteh Rivers, South Sulawesi - Adiara Firdhita Alam Nasyrah; M.Fadjar Rahardjo; Charles P.H. Simanjuntak (Jurnal Iktiologi Indonesia, 2020)
Marosatherina ladigesi is one of endemic fishes in South Sulawesi and also as ornamental fish. Anthropogenic activities such as destructive fishing and degradation caused by the dredging of sand carried M. ladigesi to the red list of threatened IUCN category as vulnerable species. Accordingly, conservation efforts are needed to maintenance fish population in its habitat. The biologic information for conservation is reproduction of fishes. This research aimed to described reproduction of Celebes rainbow fish including sex ratio, gonad maturity, gonado-somatic index, fecundity, and distribution of egg diameter in Pattunuang and Batu Puteh Rivers, South Sulawesi. This research was conducted from May 2018 to April 2019. The result showed that the sex ratio in Pattunuang and Batu Puteh rivers were 1,00:1,60 and 1,00:1,08, respectively. This species spawned from the end of dry season to the early rainy season. Fecundity of fish in Pattunuang and Batu Puteh rivers were 22-795 eggs and 69-571 eggs, respectively. Based on distribution of egg diameter, Celebes rainbowfish categorized as total spawner. For the conservation of this species is recommended to catch restrictions in the spawning season and for male fish, and needs to be proposed the conservation in situ to determine both of rivers as reservoir area because these habitats are a source of germplasm. Abstrak Marosatherina ladigesi adalah salah satu ikan endemik Sulawesi Selatan dan juga sebagai ikan hias yang telah menguasai pasar internasional. Kegiatan antropogenik seperti penangkapan yang merusak lingkungan dan degradasi akibat pengerukan pasir membawa ikan ini dalam daftar merah IUCN kategori rentan terhadap kepunahan. Upaya konservasi agar ikan endemik tetap lestari, salah satunya diperlukan informasi kajian aspek reproduksi. Penelitian ini bertujuan mengkaji aspek reproduksi ikan beseng-beseng meliputi nisbah kelamin, tingkat kematangan gonad, indeks kematangan gonad, fekunditas, dan sebaran diameter telur di Sungai Pattunuang dan Sungai Batu Puteh, Sulawesi Selatan. Penelitian dilakukan dari Mei 2018 hingga April 2019. Hasil penelitian menunjukkan bahwa nisbah kelamin ikan beseng-beseng di Sungai Patunnuang dan Sungai Batu Puteh masing-masing adalah 1,00:1,60 dan 1,00:1,10. Ikan ini memijah pada akhir musim kemarau dan awal musim penghujan. Fekunditas ikan di S. Pattunuang dan S. Batu Puteh masing-masing adalah 22 – 795 butir dan berkisar 69 – 571 butir. Berdasarkan pola sebaran diameter telur, ikan beseng-beseng memiliki tipe pemijahan serempak. Pengelolaan sumber daya ikan beseng-beseng adalah pembatasan penangkapan saat musim pemijahan khususnya ikan jantan dan perlu diusulkan konservasi in situ kedua sungai sebagai daerah perlindungan ikan (reservat) karena merupakan sumber pasma nutfah.